Family of Enneper Minimal Surfaces - Erhan Güler (Mathematics, 2018)
We consider a family of higher degree Enneper minimal surface <semantics> E m </semantics> for positive integers m in the three-dimensional Euclidean space <semantics> E 3 </semantics> . We compute algebraic equation, degree and integral free representation of Enneper minimal surface for <semantics> m = 1 , 2 , 3 </semantics> . Finally, we give some results and relations for the family <semantics> E m </semantics> .